Establishing an Animal Model of Single-Sided Deafness in Chinchilla lanigera. (December 2019) - Banakis Hartl, Renee M.; Greene, Nathaniel T.; Benichoux, Victor; Dondzillo, Anna; Brown, Andrew D.; Tollin, Daniel J.
Objectives: (1) To characterize changes in brainstem neural activity following unilateral deafening in an animal model. (2) To compare brainstem neural activity from unilaterally deafened animals with that of normal-hearing controls. Study Design: Prospective controlled animal study. Setting: Vivarium and animal research facilities. Subjects and Methods: The effect of single-sided deafness on brainstem activity was studied in Chinchilla lanigera . Animals were unilaterally deafened via gentamycin injection into the middle ear, which was verified by loss of auditory brainstem responses (ABRs). Animals underwent measurement of ABR and local field potential in the inferior colliculus. Results: Four animals underwent chemical deafening, with 2 normal-hearing animals as controls. ABRs confirmed unilateral loss of auditory function. Deafened animals demonstrated symmetric local field potential responses that were distinctly different than the contralaterally dominated responses of the inferior colliculus seen in normal-hearing animals. Conclusion: We successfully developed a model for unilateral deafness to investigate effects of single-sided deafness on brainstem plasticity. This preliminary investigation serves as a foundation for more comprehensive studies that will include cochlear implantation and manipulation of binaural cues, as well as functional behavioral tests.